A Randomised Trial Examining Cardiovascular Morbidity and All-Cause Mortality 24 years Following General Health Checks: the Ebeltoft Health Promotion Project (EHPP) - Martin Bernstorff; Pia Deichgræber; Niels Henrik Bruun; Else-Marie Dalsgaard; Morten Fenger-Grøn; Torsten Lauritzen (BMJ Open)
Introduction Global prevalence of risk factors for cardiovascular disease (CVD) and all-cause mortality is increasing. Treatments are available but can only be implemented if individuals at risk are identified. General health checks have been suggested to facilitate this process.Objectives To examine the long-term effect of population-based general health checks on CVD and all-cause mortality.Design and setting The Ebeltoft Health Promotion Project (EHPP) is a parallel randomised controlled trial in a Danish primary care setting.Participants The EHPP enrolled individuals registered in the Civil Registration System as (1) inhabitants of Ebeltoft municipality, (2) registered with a general practitioner (GP) participating in the study and (3) aged 30–49 on 1 January 1991. A total of 3464 individuals were randomised as invitees (n=2000) or non-invitees (n=1464). Of the invitees, 493 declined. As an external control group, we included 1 511 498 Danes living outside the municipality of Ebeltoft.Interventions Invitees were offered a general health check and, if test-results were abnormal, recommended a 15–45 min consultation with their GP. Non-invitees in Ebeltoft received a questionnaire at baseline and were offered a general health check at year 5. The external control group, that is, the remaining Danish population, received routine care only.Outcome measures HRs for CVD and all-cause mortality.Results Every individual randomised was analysed. When comparing invitees to non-invitees within the municipality of Ebeltoft, we found no significant effect of general health checks on CVD (HR=1.11 (0.88; 1.41)) or all-cause mortality (HR=0.93 (0.75; 1.16)). When comparing invitees to the remaining Danish population, we found similar results for CVD (adjusted HR=0.99 (0.86; 1.13)) and all-cause mortality (adjusted HR=0.96 (0.85; 1.09)).Conclusion We found no effect of general health checks offered to the general population on CVD or all-cause mortality.Trial registration number NCT00145782; 2015-57-0002; 62908, 187.